Distinct subcellular localization of alternative splicing variants of EFA6D, a guanine nucleotide exchange factor for Arf6, in the mouse brain. Issue 13 (16th June 2016) - Fukaya, Masahiro; Ohta, Shingo; Hara, Yoshinobu; Tamaki, Hideaki; Sakagami, Hiroyuki
ABSTRACT: EFA6D (guanine nucleotide exchange factor for ADP‐ribosylation factor 6 [Arf6]D) is also known as EFA6R, Psd3, and HCA67. It is the fourth member of the EFA6 family with guanine nucleotide exchange activity for Arf6, a small guanosine triphosphatase (GTPase) that regulates endosomal trafficking and actin cytoskeleton remodeling. We propose a classification and nomenclature of 10 EFA6D variants deposited in the GenBank database as EFA6D1a, 1b, 1c, 1d, 1s, 2a, 2b, 2c, 2d, and 2s based on the combination of N‐terminal and C‐terminal insertions. Polymerase chain reaction analysis showed the expression of all EFA6D variants except for variants a and d in the adult mouse brain. Immunoblotting analysis with novel variant‐specific antibodies showed the endogenous expression of EFA6D1b, EFA6D1c, and EFA6D1s at the protein level, with the highest expression being EFA6D1s, in the brain. Immunoblotting analysis of forebrain subcellular fractions showed the distinct subcellular distribution of EFA6D1b/c and EFA6D1s. The immunohistochemical analysis revealed distinct but overlapping immunoreactive patterns between EFA6D1b/c and EFA6D1s in the mouse brain. In immunoelectron microscopic analyses of the hippocampal CA3 region, EFA6D1b/c was present predominantly in the mossy fiber axons of dentate granule cells, whereas EFA6D1s was present abundantly in the cell bodies, dendritic shafts, and spines of hippocampal pyramidal cells. These results provide the first anatomical evidence suggesting the functional diversity of EFA6D variants, particularly EFA6D1b/c and EFA6D1s, in neurons. J. Comp. Neurol. 524:2531–2552, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The authors demonstrate distinct localization of splicing variants of EFA6D, an Arf6‐specific GEF, in the mouse brain. In particular, in the hippocampus, EFA6D1b/c and EFA6D1s predominantly localize at mossy fiber axons and somatodendritic components of pyramidal cells, respectively. These findings provide anatomical evidence suggesting the functional diversity of EFA6D variants in neurons.